POTENSI PELARUT ETIL ASETAT PADA EKSTRAKSI FLAVANOID DARI TANAMAN CIPLUKAN (Physalis angulata L.) - Sylviningrum, Thianti; Rianto, Bayu Dwi; Agamonanza, Freddy; Ardinas, Shinta Prima (Medical and Health Journal, 2024)
The ciplukan plant (Physalis flavonoi L.) is widely used as a traditional medicine because it contains various bioactive compounds such as flavonoids and physalin. The purpose of this study was to identify and measure the total flavonoid content of ciplukan extracts in various solvents. Ciplukan was extracted by maceration using ethanol, n-hexane and ethyl acetate solvents. Flavonoids were identified by UV-Vis spectrophotometry at 510 nm wavelength. Total flavonoid content was measured based on the calibration curve of quercetin as the standard of comparison. The highest yield of ciplukan extract was obtained from ethanol solvent (18.5%), followed by n-hexane and ethyl acetate. The highest absorbance and total flavonoid content were found in the ethyl acetate extract, which were 0.1162 and 3,709.01 μg/g. Flavonoids from Ciplukan extract were identified most optimally in the semipolar solvent ethyl acetate compared to the polar solvent ethanol and nonpolar n-hexanes. The conclusion of this study is that ethyl acetate extract has the potential to be developed as an herbal medicinal material.